2023
DOI: 10.1093/femsre/fuad022
|View full text |Cite
|
Sign up to set email alerts
|

The small intestine: dining table of host–microbiota meetings

Abstract: Growing evidence suggests the importance of the small intestinal bacteria in the diet-host-microbiota dialogue in various facets of health and disease. Yet, this body site is still poorly explored and its ecology and mechanisms of interaction with the host are just starting to be unraveled. In this review, we describe the current knowledge on the small intestinal ecology, its composition and diversity, and how the intestinal bacteria in homeostatic conditions participate in nutrient digestion and absorption. W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(8 citation statements)
references
References 325 publications
1
7
0
Order By: Relevance
“…To mimic the small intestinal condition accurately, the pH of MRS broth was adjusted to 6.5, which was regarded as consistent with the real situation in the small intestine. [ 34 ] We found that L. reuteri and L. paracasei showed significant differences in response to myoglobin and hemin, which was consistent with sequencing results. In addition, LEfSe analysis identified L. reuteri as the differential bacterium between the HMb and Hhe groups.…”
Section: Discussionsupporting
confidence: 87%
“…To mimic the small intestinal condition accurately, the pH of MRS broth was adjusted to 6.5, which was regarded as consistent with the real situation in the small intestine. [ 34 ] We found that L. reuteri and L. paracasei showed significant differences in response to myoglobin and hemin, which was consistent with sequencing results. In addition, LEfSe analysis identified L. reuteri as the differential bacterium between the HMb and Hhe groups.…”
Section: Discussionsupporting
confidence: 87%
“…Approximately ~1 L to 1.5 L of saliva containing ~10 11 oral bacterial cells daily reaches the intestinal tract. While many oral bacteria are destroyed, evidence showed that a significant number reach the gut [65], stimulate the immune system, and, with predisposing influences, can cause pathology [51]. The indirect mechanism implies that bacteria and inflammatory cytokines obtain access to the systemic circulation and then reach the gut or influence gut response.…”
Section: Subgingival Dysbiosis and Gut Dysbiosismentioning
confidence: 99%
“…While these studies have provided valuable insights into the compositional and functional changes associated with obesity 1 , the FM represents only a fraction of the gastrointestinal tract (GIT) microbiome. Particularly, the upper small intestine (USI) is of great interest due to its crucial functions in food digestion, nutrient sensing, absorption, enterohormone production, and metabolic homeostasis 2,3 .…”
Section: Main Textmentioning
confidence: 99%
“…While studies in rodents demonstrated the causal influence of the USI microbiome (USIM) on metabolic regulation, clinical investigations concerning the USIM in human obesity, remain limited and contradictory 3 . There is a pressing need for further research to elucidate the intricate interplay between lifestyle, the USIM, and metabolic health in humans 2,3 .…”
Section: Main Textmentioning
confidence: 99%